Blacking out - Lengwiler, Yvan (Universität Basel, Wirtschaftswissenschaftliche Fakultät, 2020)
The partial shutdown of the economy following the outbreak of the COVID-19 pandemic has highlighted the lack of measurements of economic activity that are available with a short lag and at high frequency. The consumption of electricity is a candidate for such a proxy.
10419/240416
Keywords: Graue Literatur; COVID-19; electricity; seasonal adjustment; weather data